Impact of antiphospholipid syndrome on placenta and uterine NK cell function: insights from a mouse model - Martirosyan, A; Kriegova, E; Savara, J; Abroyan, L; Ghonyan, S; Slobodova, Z; Nesnadna, R; Manukyan, Gayane (Scientific reports, 2024)
Antiphospholipid syndrome (APS) is associated with recurrent pregnancy morbidity, yet the underlying mechanisms remain elusive. We performed multifaceted characterization of the biological and transcriptomic signatures of mouse placenta and uterine natural killer (uNK) cells in APS. Histological analysis of APS placentas unveiled placental abnormalities, including disturbed angiogenesis, occasional necrotic areas, fibrin deposition, and nucleated red blood cell enrichment. Analyses of APS placentas showed a reduced cell proliferation, lower protein content and thinning of endothelial cells. Disturbances in APS trophoblast cells were linked to a cell cycle shift in cytotrophoblast cells, and a reduced number of spiral artery-associated trophoblast giant cells (SpA-TGC). Transcriptomic profiling of placental tissue highlighted disruptions in cell cycle regulation with notable downregulation of genes involved in developmental or signaling processes. Cellular senescence, metabolic and p53-related pathways were also enriched, suggesting potential mechanisms underlying placental dysfunction in APS. Thrombotic events, though occasionally detected, appeared to have no significant impact on the overall pathological changes. The increased number of dysfunctional uNK cells was not associated with enhanced cytotoxic capabilities. Transcriptomic data corroborated these findings, showing prominent suppression of NK cell secretory capacity and cytokine signaling pathways. Our study highlights the multifactorial nature of APS-associated placental pathologies, which involve disrupted angiogenesis, cell cycle regulation, and NK cell functionality.
Keywords: Pregnancy; Trophoblasts; Placenta; Cell proliferation; Cell Proliferation; Animals; stanovení celkové genové exprese; Anti-β2GPI antibodies; Mice; Mouse model; Female; Antiphospholipid Syndrome; modely nemocí na zvířatech; proliferace buněk; ženské pohlaví; Uterus; NK cells; buňky NK; Killer Cells, Natural; placenta; zvířata; trofoblasty; Endothelial cells; Transcriptome; Gene Expression Profiling; transkriptom; Antiphospholipid syndrome; uterus; RNAseq; těhotenství; Disease Models, Animal; myši; antifosfolipidový syndrom